Benthic Cyanobacterial Mats in the High Arctic: Multi-Layer Structure and Fluorescence Responses to Osmotic Stress - Lionard, Marie; Péquin, Bérangère; Lovejoy, Connie; Vincent, Warwick F. (Frontiers in Microbiology, 2012)
Cyanobacterial mats are often a major biological component of extreme aquatic ecosystems, and in polar lakes and streams they may account for the dominant fraction of total ecosystem biomass and productivity. In this study we examined the vertical structure and physiology of Arctic microbial mats relative to the question of how these communities may respond to ongoing environmental change. The mats were sampled from Ward Hunt Lake at the northern coast of Arctic Canada, and were composed of three visibly distinct layers. Microsensor profiling showed that there were strong gradients in oxygen within each layer, with an overall decrease from 100 % saturation at the mat surface to 0 %, at the bottom, accompanied by an increase of 0.6 pH units down the profile. 16S rRNA gene clone libraries revealed the presence of Oscillatorian sequences throughout the mat, while Nostoc related species dominated the two upper layers, and Nostocales and Synechococcales sequences were common in the bottom layer. HPLC analyses showed a parallel gradient in pigments, from high concentrations of scytonemin in the upper layer to increasing zeaxanthin and myxoxanthin in the bottom layer, and an overall shift from photoprotective to photosynthetic carotenoids down the profile. Climate change is likely to be accompanied by increased evaporation and osmotic stress of the littoral mat communities. To assess their capacity to adjust to rising osmolarities, mat sections were exposed to a gradient of increasing salinities, and PAM measurements of in vivo chlorophyll fluorescence were made to assess changes in maximum quantum yield. The results showed that the mats were tolerant of up to a 46-fold increase in salinity. These features imply that cyanobacterial mats are resilient to ongoing climate change, and that in the absence of major biological perturbations, these vertically structured communities will continue to be a prominent feature of polar aquatic ecosystems.